VILLAGE ECONOMIC WELFARE THROUGH THE COGNITIVE ROLE OF BUMDES HUMAN RESOURCES TO IMPROVE COMPETITIVENESS LOCAL WISDOM PRODUCTS OF SERDANG BEDAGAI - Rodi Syafrizal (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study explores the role of cognitive aspects of human resources (HR) in strengthening the performance of Village-Owned Enterprises (BUMDes) to increase the competitiveness of local wisdom-based products in Serdang Bedagai Regency. Although the number of BUMDes established nationally is quite significant, only a small proportion successfully contributes to rural economic growth. Using qualitative descriptive methods, data were collected through interviews, observations, and literature analysis to identify cognitive gaps among BUMDes managers in recognizing opportunities, managing resources, and innovating business strategies. The findings indicate that BUMDes often fail to align local potential with market needs, resulting in limited economic impact. Furthermore, the lack of standardized product development and market-oriented innovation weakens competitiveness. This study emphasizes that strengthening HR cognitive skills such as managerial capacity, market literacy, and an entrepreneurial mindset, combined with the operationalization of Islamic principles of maslahah into measurable performance indicators, can significantly improve the effectiveness of BUMDes. This study concludes that BUMDes with strong cognitive HR capabilities are better positioned to develop local products based on the creative economy, preserve village potential, and contribute to rural welfare. Practical implications are offered through an eight-step intervention model, including capacity audit, product prototyping, standardization, branding, and the creation of a maslahah-based performance dashboard.